El Emprendimiento Comunitario Como Resultado De La Vinculación Social Universitaria Para El Fortalecimiento De Proyectos Productivos - Olivares, Giselle; Liévano, Jahicela; Ruiz, Maythe (European Scientific Journal, ESJ, 2018)
The university is an institution with a social commitment that trains professionals in different fields. In addition to the substantive functions, referred to higher education as teaching, research and dissemination of culture, bonding arises as an increasingly important activity, which is fundamental because it is associated with strengthening the productive and social sectors. Under this premise, the Universidad Juárez Autónoma de Tabasco in Mexico has a strategic axis focused on linking to development in which different programs operate, including those of social inclusion for the benefit of communities in the region. As a consequence, the present investigation of qualitative and exploratory scope is developed under the case study design, with the objective of explaining how community entrepreneurship can be consolidated from the academy fostering social bonding; documenting an institutional project that was favorable both for the institution through social ties with Tabasco communities, and for a group of small producers of the entity. The community project was developed through an alliance between students, research professors and entrepreneurship experts. The results showed that the link is an effective instrument to strengthen the relevance of the university, to meet social needs, support government agencies to make their programs more efficient and effective, as well as feedback the training processes of the university itself, for the benefit of different communities of the state of Tabasco in Mexico.